Analisis Pengaruh Gaya Hidup Terhadap Keputusan Pembelian Sepeda Motor Honda Beat Di Pekanbaru - Indra Mandala Putra; Jushermi '; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect Lifestyle consisting of variable Activity, interest and Opinion on the purchasing decisions of Honda Beat motorcycle In Pekanbaru. The method of analysis used is multiple regression analysis, hypothesis test consisting of Partial Test (Test Statistic t), Simultaneous test (Test Statistic F) and test the coefficient of determination (R2). Workmanship performed using SPSS 17. Data used are primary and secondary data. This study used a sample of 100 respondents in the study were taken using Slovin formula. The results of this study demonstrate that the analysis of the data by the method of multiple linear regression analysis showed that lifestyle consists of a variable Activity, interest positive and significant impact on the purchasing decisions of Honda Beat motorcycle in Pekanbaru. while the variable opinion positive but not significant effect on the purchasing decision of Honda Beat motorcycle. Based on the t test of the three independent variables that are the most dominant influence purchasing decisions Honda Beat in Pekanbaru is a variable interest (Interest) X2 with a β value of 0.874. Analysis of the coefficient of determination obtained Adjusted R2 value of 27% which means the dependent variable is the purchase decision process can be described by using the free variables Activity, interest and Opinion and the remaining 73% is influenced by other variables not included in this study.Keyword : Activities, Interest, Opinions and Purchasing Decision.